Examining the changes in the prevalence of Hepatitis a in Türkiye: systematic review and metaanalysis - Özge Karakaya Suzan; Murat Bektaş; Mustafa Altındiş; Özge Kaya; Ayşe Eroğlu; Serap Çetinkaya Özdemir; Seda Tecik; Ahmet Naci Emecen; Nursan Çınar (BMC, 2024)
Abstract Background The incidence of Hepatitis A is increasing worldwide. Yearly classification of Hepatitis A Seroprevalence for different times in different regions of Türkiye allows indirect measurement of year-specific incidence rates of HAV infection and can be considered the best way to define Hepatitis A status. This study aimed to examine the change in the incidence of hepatitis A by systematically evaluating the available data on the seroprevalence of anti-HAV antibodies in the Turkish population. Methods Studies published between First January, 2000- 31 December 2023 that meet the inclusion criteria searched between 16.09.2023 and 31.01.2024 in nine databases (MEDLINE, Web of Science, PubMed, ScienceDirect, Scopus, Eric, CINAHL Complate, TR DİZİN, TÜBİTAK Ulakbim). Independently by two reviewers evaluated all titles and abstracts with consensus-based decision making. The Joanna Briggs Institution (JBI) Analytical Cross Sectional Studies and Prevelance Studies list were used in this study. Pooled prevalence was calculated using 95% confidence intervals. Heterogeneity between studies was assessed by Cochrane's Q and I2. The random effect model was selected by Cochrane's Q and I2. Funnel plots were used for publication bias. The data were analyzed via Jamovi 1.2.22. Results Data were extracted from 63 studies. Pooled prevalence was calculated using 95% confidence intervals. Funnel plots were used for publication bias. In this meta-analysis, data were obtained from all geographical regions of Türkiye, and the general prevalence of Hepatitis A in the population was found to be 53% [95% CI 0.47, 0.59; I2 = 99.94%]. In subgroup analysis conducted by year, the prevalence of hepatitis A was 45% [95% CI 0.22, 0.67; I2 = 99.8%] between 2002 and 2006, 52% [95% CI 0.39, 0.65; I2 = 99.54%] between 2007 and 2011, 60% [95% CI 0.49, 0.70; I2 = 99.9%] between 2012 and 2016, and 51% [95% CI 0.41, 0.61; I2 = 99.97%] as of 2017. Additionally, a systematic review revealed that vaccination, socioeconomic status, and sex may also affect HAV seroprevalence. Conclusions HAV seroprevalence in Türkiye; It was observed that it increased between 2002 and 2016 and decreased until today as of 2017. This systematic review provide a comprehensive overview of HAV virus epidemiology and identify key knowledge gaps, contributing crucial information for influencing factors. Trial registration PROSPERO ID = CRD42023464384.